Pengaruh Lingkungan Keluarga Islami Terhadap Self Eficacy Siswa Kelas VII (Studi Madrasah Tsanawiyah Nurul Iman Bani Sulton) - Millata Hanifa; Siti Anisa Musyana; Miftahul Ulfa; Royhan Imamul Muttaqin (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2026)
This study aims to determine the influence of Islamic Family Environment on Self- Efficacy and to determine the Self-Efficacy induced by Islamic Family Environment in seventh-grade students of Madrasah Tsanawiyah Nurul Iman Bani Sulton. This study uses a quantitative correlational approach. The population in this study were seventh-grade students of Madrasah Tsanawiyah Nurul Iman Bani Sulton, with a sample of 17 students. Data collection used a questionnaire, and data analysis techniques used research instrument testing, prerequisite analysis testing, and hypothesis testing using SPSS 15 software. The results showed that the Islamic Family Environment had a 95.6% influence on the Self-Efficacy of seventh-grade students at Madrasah Tsanawiyah Nurul Iman Bani Sulton, as seen from the coefficient of determination test. The remaining 4.4% was influenced by other factors not examined in this study.